2019
DOI: 10.1016/j.wocn.2019.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Twenty-eight years of vowels: Tracking phonetic variation through young to middle age adulthood

Abstract: Research on age-related changes in speech has primarily focused on comparing "young" vs. "elderly" adults. Yet, listeners are able to guess talker age more accurately than a binary distinction would imply, suggesting that acoustic characteristics of speech change continually and gradually throughout adulthood. We describe acoustic properties of vowels produced by eleven talkers based on naturalistic speech samples spanning a period of 28 years, from ages 21 to 49. We nd that the position of vowels in F1/F2 spa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 90 publications
0
20
0
Order By: Relevance
“…Although our illustration may suggest a unidirectional information cascade from the environment to retrieval, our framework does not preclude a dynamic flow, with later components influencing earlier ones. For example, pronunciation tends to change with age, likely as a result of continued experience and efforts to optimize discrimination between words [27,28], and these perceptual/motor changes can be seen as influences on the linguistic environment of those exposed to the language of older speakers. In what follows, we review past evidence concerning each of these components below.…”
Section: A Framework For Understanding the Aging Lexiconmentioning
confidence: 99%
“…Although our illustration may suggest a unidirectional information cascade from the environment to retrieval, our framework does not preclude a dynamic flow, with later components influencing earlier ones. For example, pronunciation tends to change with age, likely as a result of continued experience and efforts to optimize discrimination between words [27,28], and these perceptual/motor changes can be seen as influences on the linguistic environment of those exposed to the language of older speakers. In what follows, we review past evidence concerning each of these components below.…”
Section: A Framework For Understanding the Aging Lexiconmentioning
confidence: 99%
“…Summary figure illustrating the age ranges from a range of speech production studies. Design inspired from Gahl and Baayen (2019)…”
Section: Introductionmentioning
confidence: 99%
“…Our study therefore shows that speakers acquired greater articulatory practice and this practice becomes part of their mental lexicon. Just recently, investigating speech production of the same speakers over a periode of 28 years, Gahl and Baayen (2019) have shown that the positions of vowels in the F1/F2 space shift towards the periphery, the older the speakers are, making them more discriminable. Thus, the changes attested in the present study do not only mirror improved kinematic skills but also greater lexical proficiency.…”
Section: Discussionmentioning
confidence: 99%